Assistive technology in resource-limited environments: a scoping review. (17th February 2017) - Matter, Rebecca; Harniss, Mark; Oderud, Tone; Borg, Johan; Eide, Arne H.
Abstract: Purpose: It is estimated that only 5–15% of people in low and middle income countries (LMICs) who need assistive technologies (AT) have access to them. This scoping review was conducted to provide a comprehensive picture of the current evidence base on AT within LMICs and other resource limited environments. Method: The scoping review involved locating evidence, extracting data, and summarizing characteristics of all included research publications. Results: Of the 252 publications included, over 80% focused on types of AT that address mobility (45.2%) and vision (35.5%) needs, with AT types of spectacles and prosthetics comprising over 50% of all publications. Evidence on AT that addresses hearing, communication, and cognition is the most underrepresented within the existing evidence base. The vast majority of study designs are observational (63%). Conclusions: Evidence on AT in resource-limited environments is limited in quantity and quality, and not evenly distributed across types of AT. To advance this field, we recommend using appropriate evidence review approaches that allow for heterogeneous study designs, and developing a common language by creating a typology of AT research focus areas. Funders and researchers must commit much greater resources to the AT field to ameliorate the paucity of evidence available. Implications for Rehabilitation: An increase in the quality and quantity of research is required in resource limited environments, where 80% of the global population of people with disabilities reside. Improved and increased evidence is needed to identify and understand needs, inform policy and practice, and assess progress made in increasing access to and availability of appropriate AT. Over 80% of the existing research publications on assistive technologies in resource limited environments address mobility and vision. More research is needed on AT that address hearing, communication and cognition. The use of a common language would facilitate the advancement of the global AT research field. Specifically there is a need for researchers to use a common definition of AT (i.e., ISO 9999) and typology of AT research focus areas.